Analysis of the multicomponent ALEX array data to examine patterns of sensitization in Cape Town, South Africa - Pedretti, Sarah; Sittmann, Alexander; Von Hagen, Arné; Peter, Jonny (Frontiers in Allergy, 2025)
IntroductionThis study analysed allergen sensitization patterns in Cape Town, a biodiversity-rich region with a Mediterranean climate, using ALEX® and ALEX²® multiplex component-resolved diagnostics tools. It aimed to address gaps in allergen sensitisation pattern data and complement aerobiological monitoring.Methods and resultsA retrospective review of 708 adults and children attending two tertiary allergy clinics (2019–2024) found that house dust mites were the most common allergens, affecting 50%–60% of participants, with Der p 23 particularly prevalent (53%). Grass pollen sensitization was also high (46%), with 85% sensitised to the C4 grass Bermuda. Tree pollen sensitisation occurred in 29% with 14% sensitised to a diverse range of trees but neither London plane nor Cypress currently recommended in limited testing panels. Common food allergens included fruits (30%), seafood (27%), and nuts (25%), often linked to pollen cross-reactivity.ConclusionOur study confirms a known pattern of aeroallergen sensitisation for a coastal temperate region, with increasing pollen sensitisation, particular C4 grasses. Clinicians should be aware of the diversity of tree pollen sensitisation, cross-reactivity patterns between food and pollen sensitisations and rates of minor allergen sensitisations for Blomia and animal danders when considering allergen-immunotherapies.